Analysis of brain‐facial muscle connection in the static fractal visual stimulation. Issue 2 (1st September 2020) - Soundirarajan, Mirra; Babini, Mohammad Hossein; Sim, Sue; Nathan, Visvamba; Subasi, Abdulhamit; Namazi, Hamidreza
Abstract: Analysis of the coupling among the brain and various organs activities is an exciting and new research area of biomedical signal analysis. We decode the correlation among the brain and facial muscle activities during rest and visual stimulation. Fractal analysis is utilized to evaluate the alterations of complexity. In this study, we present different images with different complexities to participants and evaluate how complex structures of electromyography (EMG) signals and electroencephalography (EEG) signals are related. The findings indicate that the alteration of EMG signals' complexity was significant ( P value = .0001). Besides, more significant alterations in the EMG and EEG signals' complexities in response to the stimuli with higher complexities were observed. We conclude that the brain and facial muscles activities are related. We can analyze other physiological signals using this method to investigate their relationship with the brain.